Social support and the effects of the COVID-19 pandemic among a cohort of people living with HIV (PLWH) in Western Kenya - Adel Mburia-Mwalili; Karla D. Wagner; Edith Kamaru Kwobah; Lukoye Atwoli; Maurice Aluda; Brianna Simmons; Jayne Lewis-Kulzer; Suzanne Goodrich; Kara Wools-Kaloustian; Jennifer L. Syvertsen (Public Library of Science (PLoS), 2023)
As coronavirus disease (COVID-19) was declared a pandemic in 2020, countries around the world implemented various prevention strategies, such as banning of public and social gatherings, restriction in movement, etc. These efforts may have had a deleterious effect on already vulnerable populations, including people living with HIV (PLWH). PLWH were concerned about contracting COVID-19, the impact of COVID-19 on their social networks that provide social support, and the continued availability of antiretroviral medications during the pandemic. In addition, their mental health may have been exacerbated by the pandemic. The purpose of this study was to explore pandemic-related concerns among a cohort of PLWH in Kenya and investigate social support factors associated with symptoms of depression and anxiety. This study is part of a larger cohort study that recruited from two clinics in Western Kenya. Data are drawn from 130 PLWH who participated in two phone surveys about experiences during the pandemic in 2020 and 2021. Participants reported a variety of concerns over the course of the pandemic and we documented statistically significant increases in symptoms of depression and anxiety over time, which affected some participants' ability to adhere to their antiretroviral medication. However, a small but statistically significant group of participants reached out to expand their networks and mobilize support in the context of experiencing mental health and adherence challenges, speaking to the importance of social support as a coping strategy during times of stress. Our findings call for holistic approaches to HIV care that consider the broader political, economic, and social contexts that shape its effectiveness.